The gastrointestinal side effects of chemotherapy in lung cancer patients - Słowik-Gabryelska, Anna; Opozda, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2000)
The fact, that digestive tract toxicity of chemotherapy to is very high, and malnutrition, bad biological state, the gastrointestinal lesions and other coexisting diseases enlarges it, made us to examine the side effects of chemotherapy in lung cancer patients. The additional motivation for these examinations was lack of publications in that matter. The aim of presented examinations was to establish the real danger of chemotherapy in lung cancer patients. Material and method: in 309 lung cancer patients, the number and intensity of gastrointestinal side effects of chemotherapy was assessed. There was established intensity of nausea/vomiting, diarrhea, oral lesions and SGOT/SGPT blood level. The intensity of side effects of chemotherapy in 5 degree WHO scale was estimated. The intensity of side effects of chemotherapy in dependence on the age, cellular type and stage of cancer, the dose and drugs combinations as well as on the results of therapy was analysed. The results: in about 80% of lung cancer patients after chemotherapy the gastrointestinal side effects were seen. There was established that, the number and intensity of side effects of chemotherapy was dependent upon the age, the doses and drugs combinations. The number and intensity of side effects of chemotherapy with age, and dose of drugs was growing. It concerns especially to Cisplatin, Vepesid and 5-Fluprouracil. The toxicity of chemotherapy upon the results of treatment was dependent. In ineffective chemotherapy the number and intensity of side effects was growing.